2018
DOI: 10.1029/2018gl077843
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Aftershocks Occur Within the Rupture Area of a Large Earthquake?

Abstract: The mainshock‐aftershock sequence is one of the fundamental characteristics of seismogenesis, yet the physical mechanism of aftershock generation remains poorly understood. The simple explanation that aftershocks are caused by the mainshock's redistribution of strain energy is not always applicable, especially for aftershocks within the mainshock slip area, where strain energy is released. Here we show that the genesis of aftershocks can be modeled using a frictionally heterogeneous fault system. We conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…asperities' of the 1942, 1958 and ruptures are separated by weak zones that typically behave aseismically, but can slip abruptly when driven by failure of neighbouring asperities -this mechanism was proposed to explain the coordinated rupture of all three asperities in a M w 8.8 earthquake in 1906. Indeed, frictional properties may vary during the course of the earthquake cycle, and patches that are conditionally stable may participate in both coseismic and aseismic slip phases Yabe and Ide [2018]. modeled a frictionally heterogeneous fault system and their quasi-dynamic numerical simulation results were able to reproduce afterslip and aftershocks occurring around and within the mainshock rupture zone.…”
mentioning
confidence: 99%
“…asperities' of the 1942, 1958 and ruptures are separated by weak zones that typically behave aseismically, but can slip abruptly when driven by failure of neighbouring asperities -this mechanism was proposed to explain the coordinated rupture of all three asperities in a M w 8.8 earthquake in 1906. Indeed, frictional properties may vary during the course of the earthquake cycle, and patches that are conditionally stable may participate in both coseismic and aseismic slip phases Yabe and Ide [2018]. modeled a frictionally heterogeneous fault system and their quasi-dynamic numerical simulation results were able to reproduce afterslip and aftershocks occurring around and within the mainshock rupture zone.…”
mentioning
confidence: 99%
“…Luo and Ampuero (2017) performed a thorough stability analysis of an infinite frictionally heterogeneous fault. Yabe and Ide (2018;hereafter YI18) reproduced aftershocks within the mainshock rupture area (e.g., Beroza and Zoback 1993;Woessner et al 2006) by considering the partial rupture of a frictionally heterogeneous fault. Dublanchet et al (2013) and YI18 reported foreshocks before the mainshock, though no previous study has investigated the causes of variations in foreshock activity.…”
Section: Introductionmentioning
confidence: 99%
“…Several earthquake sequence models add frictional heterogeneity (a mixture of velocity‐weakening and ‐strengthening regions) to produces on‐fault aftershocks. For example, Yabe and Ide (2018) were successful in reproducing on‐fault aftershocks for a single planar fault by varying the sign of a − b . Kaneko and Lapusta (2008) also studied the earthquake nucleation process and aftershock sequences in the transition zone of a − b .…”
Section: Discussionmentioning
confidence: 99%
“…From the physical perspective, rerupture of part of the mainshock fault as an aftershock requires very high‐speed healing and reloading. Although some recent numerical studies show that rerupture of the main fault is possible in a subset of the parameter space (Barbot, 2019b; Cattania, 2019; Yabe & Ide, 2018), many earthquake sequence models on a flat fault with spatially variable friction often show seismic quiescence after the largest events occur (Aochi & Ide, 2009; Dublanchet et al., 2013). Therefore, it is reasonable to assume that most aftershocks are the ruptures of subsidiary faults surrounding major faults that are ruptured as mainshock, at least for intraplate earthquakes on immature faults (i.e., faults with short slip histories, which have been shown to have a more complex architecture than long‐lived, mature faults [Ben‐Zion & Sammis, 2003; Manighetti et al., 2007]), such as the Tottori event.…”
Section: Introductionmentioning
confidence: 99%